Mind the gap: Strategies from California on navigating access to public hearings - Bukalova, Dominika and Maland, Elizabeth (Public Administration Review)
Public hearings play a critical role in U.S. local government. The evolution of public access to local government hearings and its related challenges have not been documented in a systematic way to encourage research and collaborative scholarship between practitioners and scholars. This article seeks to begin the dialogue by offering seven strategies for navigating access to public hearings in local government. In recent years, local governments have faced increasing pressure to keep pace with evolving technologies while balancing competing budget priorities and assuming a growing role in addressing policy issues that were previously the focus of state and national governments. The COVID-19 pandemic context has presented further complexity. Left unaddressed, these challenges contribute to a widening gap between what is administratively sustainable versus politically acceptable. The strategies suggested address current challenges, attempt to bridge the gap between what is administratively sustainable and politically acceptable, and propose avenues for further study.- Reproduced